PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA BAGI HASIL PADA BELANJA MODAL - Widiasih, Ni Nyoman; Gayatri, . (E-Jurnal Akuntansi; Vol 18 No 3 (2017), 2017)
The purpose s of this study are to determine the influence of local revenues, general allocation funds, and revenue-sharing on capital expenditure as well as to determine the occurrence of the phenomenon of flypaper. The study was conducted in the period 2010-2015. Its population is eight regencies and one city in Bali province. The sampling method used was saturated sampling so that the sample in this study were all members of the population. The data used is secondary data APBD Realization Report. The analysis technique used is multiple linear regression. The test results show that the local revenue and general allocation fund positive effect on capital expenditure, while the revenue-sharing negative effect on capital spending. Flypaper phenomenon does not occur in capital expenditure.
Keywords: Local Revenues, GAF, Flypaper Effect